Interpreting pedagogical beliefs: English language teaching in Islamic educational institutions - Ilyas, Hamzah Puadi; Tarmini, Wini (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Within Islamic educational institutions, English language instruction embodies a dual focus: the cultivation of linguistic proficiency and the transmission of ethical and spiritual values. This qualitative phenomenological study investigates the pedagogical beliefs of English teachers in Madrasah Aliyah (Islamic senior high schools) and their subsequent enactment in classroom practice. The research addresses two core questions: (1) What epistemological and pedagogical beliefs underpin their approach to English language teaching? and (2) How are these beliefs operationalized in instructional strategies and teacher-student dynamics? Conducted across three urban centers in Indonesia—Jakarta, Bogor, and Tangerang—the study engaged eleven experienced English teachers, each with over five years of service. Data were gathered via semi-structured interviews and non-participant classroom observations, then subjected to thematic analysis. Findings reveal that teachers conceptualize English not merely as a global lingua franca but as a vehicle for fostering ethical conduct and spiritual consciousness. This belief system manifests in pedagogical actions such as adapting secular textbook content, intentionally embedding Islamic principles into lessons, and modeling values of respect and integrity. The study concludes that a strong alignment exists between teacher belief and pedagogical practice within this faith-based context. It underscores the necessity for teacher education programs to explicitly bridge English language teaching methodologies with Islamic educational philosophy and calls upon curriculum developers to design materials that integrate linguistic and moral-ethical learning objectives.